2007
DOI: 10.1029/2006jf000631
|View full text |Cite
|
Sign up to set email alerts
|

Responses of permafrost to climate change and their environmental significance, Qinghai‐Tibet Plateau

Abstract: [1] In this paper we summarize recent research in geocryological studies carried out on the Qinghai-Tibet Plateau that show responses of permafrost to climate change and their environmental implications. Long-term temperature measurements indicate that the lower altitudinal limit of permafrost has moved up by 25 m in the north during the last 30 years and between 50 and 80 m in the south over the last 20 years. Furthermore, the thickness of the active layer has increased by 0.15 to 0.50 m and ground temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
459
1
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 722 publications
(506 citation statements)
references
References 34 publications
9
459
1
8
Order By: Relevance
“…Mean ground temperature in the cold permafrost region rose more than in the warm permafrost region [21,22]. The same result was observed in the Urengoy region in Russia [31], where the warming rate in cold permafrost regions reached 0.045°C a -1 , but only 0.030°C a -1 in warm permafrost regions.…”
Section: Temperature Variation In the Active Layer And Its Regional Dsupporting
confidence: 71%
See 2 more Smart Citations
“…Mean ground temperature in the cold permafrost region rose more than in the warm permafrost region [21,22]. The same result was observed in the Urengoy region in Russia [31], where the warming rate in cold permafrost regions reached 0.045°C a -1 , but only 0.030°C a -1 in warm permafrost regions.…”
Section: Temperature Variation In the Active Layer And Its Regional Dsupporting
confidence: 71%
“…Recent work in the area has shown that, due to global climate warming, the permafrost on the QTP has degraded remarkably, including a rise in permafrost temperature, an increase in the thickness of the active layer, and a decrease in permafrost area [21][22][23][24]. This degradation of permafrost may alter the groundwater table, resulting in more arid soil, and exacerbating desertification [21,25,26]. By analyzing the thermodynamic processes of the QTP active layer, Ding et al [13] concluded that the active layer thickness (ALT) was closely related to the soil cumulative temperature at 4 cm depth, while Wu et al [15,23] showed that ALT was closely related to soil temperature at 50 cm depth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower altitude limit of permafrost has risen by 40-80 m on the TP (Wang et al 2000) with the northern boundary of permafrost having retreated 0.5-1.0 km towards the south and the southern boundary 1-2 km towards the north under the effect of the climate change (Tong and Wu 1996). Regional lowering of groundwater tables triggered by degrading permafrost has become one of the major factors responsible for the deteriorating environment, as evidenced by dropping lake water levels, shrinking wetlands, and degenerating grasslands (Cheng and Wu 2007). The degradation of permafrost can directly lead to significant degradation of alpine cold meadow and Cropland Grassland alpine cold swamp meadow, but has less influence on alpine cold steppe ecosystems .…”
Section: Permafrost Degradationmentioning
confidence: 99%
“…The degradation of permafrost can directly lead to significant degradation of alpine cold meadow and Cropland Grassland alpine cold swamp meadow, but has less influence on alpine cold steppe ecosystems . Permafrost degradation will likely cause a drier ground surface (Cheng and Wu 2007) and can also significantly affect soil properties ) and as such, might contribute to desertification on the plateau.…”
Section: Permafrost Degradationmentioning
confidence: 99%